PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI ISLAMIC BOARDING SCHOOL - Muhamad Tisna Nugraha; Uwoh Saepuloh; Uus Ruswandi; Bambang Samsul Arifin (WANIAMBEY : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to describe the implementation of Islamic Religious Education and Character in Islamic Boarding schools. The method used for this research is a qualitative method with a library research design. Whereas for the research instruments, data collecting is documentation and observation. Based on research results shows that the implementation of Islamic Religious Education and Character in Islamic Boarding School is based on the national curriculum. The learning method used is the classical learning method, such as the lecture method, the question-answer method, and the storytelling method. Meanwhile, the modern learning method is active learning, such as the PAIKEM model.